2021
DOI: 10.1177/13506501211039793
|View full text |Cite
|
Sign up to set email alerts
|

An analysis method of pressure characteristic for cylindrical intershaft gas film seal considering centrifugal expansion, rotor misalignment, and precession

Abstract: To improve the weaknesses of large leakage and wear of dual-rotor intershaft labyrinth seal in aero-engines, the cylindrical gas film seal of metal rubber with a compliant feature is proposed to substitute this conventional seal. According to the dual-rotor operating condition, an analysis method of gas film pressure is presented considering the complex condition of rotor tilt, centrifugal expansion effect, and rotor circular precession. The characteristics of gas film pressure distribution are computed and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As is well known, inter-shaft rub-impact faults between rotors can lead to a reverse whirl of the rotor. Kang et al [17] found in their study that reverse whirl caused by rotor-stator rub impact includes not only frequency components due to unbalanced excitation but also significantly large negative reverse whirl frequencies. However, in this study, the inter-shaft rub-impact excitation does not directly act on the disk position.…”
Section: Analysis Of Whirl Behavior In Dual-rotor Systems With Inter-...mentioning
confidence: 99%
See 2 more Smart Citations
“…As is well known, inter-shaft rub-impact faults between rotors can lead to a reverse whirl of the rotor. Kang et al [17] found in their study that reverse whirl caused by rotor-stator rub impact includes not only frequency components due to unbalanced excitation but also significantly large negative reverse whirl frequencies. However, in this study, the inter-shaft rub-impact excitation does not directly act on the disk position.…”
Section: Analysis Of Whirl Behavior In Dual-rotor Systems With Inter-...mentioning
confidence: 99%
“…The full-spectrum method was first proposed by Bently. For a detailed introduction to the theory and derivation process of the full-spectrum method, please refer to [17].…”
Section: Analysis Of Inter-shaft Rub-impact Fault Whirl Behavior Base...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al analyzed the impact of rotor eccentricity and centrifugal expansion effect on the performance of a compliant cylindrical intershaft gas film seal and proposed an analysis method for gas film pressure. However, in the study of operating parameters, the impact of eccentricity and rotational speed on sealing performance was mainly considered [23,24]. Wang et al designed a groove bottom diversion texture and studied the influence of diversion texture on the sealing performance of cylindrical gas film seals under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problem of inter-shaft sealing end face collision caused by large axial displacement of the rotor, cylindrical gas film technology has been proposed for reverse inter-shaft sealing. Hou et al [15,16] proposed a cylindrical reverse inter-shaft gas film seal with an elastic support structure and used an aeroelastic coupling calculation method to analyze the effects of rotor rotation direction, seal ring width, rotor speed, and rotor radius on sealing performance. However, the cylindrical reverse inter-shaft sealing structure of the elastic support structure is complex, making it difficult to process, install, and adjust.…”
Section: Introductionmentioning
confidence: 99%